Ancient DNA and its contribution to understanding the human history of the Pacific Islands. Issue 3 (2nd August 2018) - BEDFORD, STUART; BLUST, ROBERT; BURLEY, DAVID V.; COX, MURRAY; KIRCH, PATRICK V.; MATISOO‐SMITH, ELIZABETH; NÆSS, ÅSHILD; PAWLEY, ANDREW; SAND, CHRISTOPHE; SHEPPARD, PETER
ABSTRACT: Two recent papers, by Lipson et al . and Posth et al ., have challenged current interpretations of the initial settlement of Remote Oceania. We invited Stuart Bedford, who is an author on both papers, to outline their importance, and a number of scholars in various disciplines to comment on their findings.